2021
DOI: 10.3765/plsa.v6i1.5001
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the connection between Question Under Discussion and scalar diversity

Abstract: Previous research has revealed that different scalar expressions give rise to scalar inferences (SIs) at different rates. This variation has been termed scalar diversity. In this study, we investigate the role of Questions Under Discussion (QUDs) in explaining this variation in SI rates. Investigating 43 different scalar expressions, we first show that explicit QUDs robustly affect calculation rates: questions based on the stronger of two scalar terms lead to higher SI rates than questions promoting the weaker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Inroads have recently been made into studying such questions, e.g., by Ronai and Xiang (2021). Their Experiment 3 relates to our first question, since it proposes a way to measure which QUDs are more likely in a given context by forcing participants to choose between a QUD containing the weaker scalar term and one containing the stronger term (e.g., when describing a student, the experiment tests whether participants would be more likely to ask "Is the student intelligent?"…”
Section: Discussionmentioning
confidence: 99%
“…Inroads have recently been made into studying such questions, e.g., by Ronai and Xiang (2021). Their Experiment 3 relates to our first question, since it proposes a way to measure which QUDs are more likely in a given context by forcing participants to choose between a QUD containing the weaker scalar term and one containing the stronger term (e.g., when describing a student, the experiment tests whether participants would be more likely to ask "Is the student intelligent?"…”
Section: Discussionmentioning
confidence: 99%
“…The discovery of this variation in the rates of implicatures has led to much research devoted to explaining the phenomenon. It has been found that there are general differences between various broad types of scalar words (Van Tiel et al, 2016;Sun et al, 2018;Gotzner et al, 2018;van Tiel et al, 2019;Ronai & Xiang, 2021aSun et al, 2023).…”
Section: Scalar Diversitymentioning
confidence: 99%
“…Testing 43 lexical scales, van Tiel et al (2016) found that the range of SI rates spanned 4% to 100%. The existing body of work investigating scalar diversity has largely concentrated on identifying properties of different lexical scales that can predict how likely they are to lead to SI, thereby explaining the observed across-scale variation (Gotzner, Solt & Benz 2018;Hu, Levy & Schuster 2022;Hu, Levy, Degen & Schuster 2023;Pankratz & van Tiel 2021;Ronai & Xiang 2021Sun, Tian & Breheny 2018; van Tiel et al 2016;Westera & Boleda 2020). However, much less attention has been paid to within-scale variation: namely, how properties of the sentence a particular scalar term (old, smart) appears in affect the likelihood of SI calculation, and how these differences relate to across-scale variation, that is, scalar diversity itself.…”
Section: Previous Work On Scalar Diversitymentioning
confidence: 99%